CASE REPORT ABOUT IMMUNOTHERAPY IN MANAGEMENT OF METASTATIC RENAL CANCER: TREATMENT WITH CHECKPOINT PD-L1 AND/OR ANTI-CTLA-4 INHIBITORS: LA INMUNOTERAPIA EN EL MANEJO DEL CÁNCER RENAL METASTÁSICO: EN TRATAMIENTO CON INHIBIDORES DE CHECKPOINT PD-L1 Y/O ANTI-CTLA-4. A PROPÓSITO DE UN CASO - Malpartida-Palomino, Robert (2024)
ABSTRACT Approximately 15 percent of renal cell carcinoma (RCC) present as locally advanced or metastatic, where surgery is not curative. The prognosis of patients with advanced or metastatic CRC can vary from a few months to a few years, depending on the clinical, pathological, and radiological characteristics of the disease. The advent of the use of anti-monoclonal-based immunotherapy as checkpoint inhibitors in initial systemic therapy for advanced clear cell RCC. We will present a clinical case where immunotherapy plays a role through the use of anti-monoclonal drugs to treat a male patient with metastatic kidney disease who presents a clinical response after surgical treatment and immunotherapy for 2 years without evidence of oncological disease to date.